2019
DOI: 10.1097/rhu.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Hispanics With Rheumatoid Arthritis

Abstract: Objective The aim of this study was to evaluate referral and treatment delays by ethnicity/race in patients with rheumatoid arthritis (RA) treated at an academic rheumatology center. Methods We reviewed the medical records of all RA patients evaluated at an outpatient clinic between 2011 and 2016 to identify newly diagnosed and naive-to-treatment patients. We determined the durations between symptom onset and first rheumatology visit and time to initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Participants frequently noted that general practitioners did not discuss hearing loss or refer for testing, mirroring studies revealing disparities in specialty referrals for patients seen in primary care, such as significantly delayed or disparate referrals for Hispanic patients for chronic renal failure (Ifudu et al 1999), coronary artery or congestive heart failure (Cook et al 2009), mental healthcare for the treatment of depression and anxiety (Laomasino et al 2011), and treatment for rheumatoid arthritis (Mariam et al 2020). A lack of referral for a hearing test expressed by participants in the present study also aligns with the findings of McKee et al (2018), Carlson et al (2019), and McMahon et al (2021), whose qualitative study results revealed that primary care providers did not discuss or minimized hearing loss, screenings, or hearing devices at appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Participants frequently noted that general practitioners did not discuss hearing loss or refer for testing, mirroring studies revealing disparities in specialty referrals for patients seen in primary care, such as significantly delayed or disparate referrals for Hispanic patients for chronic renal failure (Ifudu et al 1999), coronary artery or congestive heart failure (Cook et al 2009), mental healthcare for the treatment of depression and anxiety (Laomasino et al 2011), and treatment for rheumatoid arthritis (Mariam et al 2020). A lack of referral for a hearing test expressed by participants in the present study also aligns with the findings of McKee et al (2018), Carlson et al (2019), and McMahon et al (2021), whose qualitative study results revealed that primary care providers did not discuss or minimized hearing loss, screenings, or hearing devices at appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on evidence in the literature spanning time frames of 2011-2016 and 1997-2015, respectively, African American and Hispanic patients had worse disease manifestations and outcomes than Caucasian patients with rheumatoid arthritis in the USA, which persisted even after adjusting for age and gender. 36,37 Another recent literature review, published by researchers from Nigeria and the UK, studying the diagnosis and management of rheumatoid arthritis among low-income populations in resource-poor countries, particularly in Sub-Saharan Africa, demonstrated significant health inequities. 38 Patients in these countries lacked the necessary resources (including financial resources, social support and availability of specialists) for the timely diagnosis and management of their disease, leading to disease worsening, disability and an inability to work.…”
Section: Disparities In Systemic Policies and Infrastructurementioning
confidence: 99%
“…Recent studies indicate differential risk of RA by different demographic groups (e.g., race/ethnicity, socioeconomic status (SES), educational attainment) [ 4 ]; variances in use patterns of biologic medications for different racial/ethnic groups [ 5 ]; and lower functional status across SES quintiles within these groups [ 6 ]. Additional studies found disparities in time from symptom onset to first RA treatment, especially among Hispanics [ 7 ]. However, there is still a lack of large-scale studies investigating these disparities in clinical and patient-reported outcomes (PROs) of RA by race/ethnicity groups [ 8 ].…”
Section: Introduction and Objectivementioning
confidence: 99%